PERLINDUNGAN HUKUM DALAM MENYAMPAIKAN PENDAPAT DIMUKA UMUM DI TENGAH PANDEMI COVID-19 DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Fadil Gheantoro (Gapenas Publisher, 2023)
Covid-19 that attacked Indonesia in early 2020, the pandemic that occurred has robbed many of the people's rights, many people have also been unable to carry out their activities as usual. Starting from work, school, playing, to demonstrations / expressing opinions in public places. Large-Scale Social Restrictions or PSBB is one of the government's many efforts to overcome the Covid-19 virus by limiting the activities of residents who are considered to have the potential to spread Covid-19. PSBB has affected many things, starting from school activities, the economy and democracy in terms of expressing opinions in public or demonstrations. Even though demonstrations / expressions of opinion in public places have actually been protected and stated in the 1945 Constitution in article 28F